Shrinking Civil Space? Exploring State and Civil Society Perspectives on the Contemporary Situation of Human Rights Defenders in South Asia. (December 2022) - Chaney, Paul
This study analyses state and civil society organizations' (CSOs) perspectives on the contemporary situation of human rights defenders (HRD) in South Asia using submissions to the Universal Periodic Review (UPR), the United Nations five-yearly monitoring process. The governments' UPR discourse shows how their engagement is characterized by performativity and legitimation. They appear to embrace the promotion of HRDs' rights in a way that advances governments' political legitimacy on the international stage. Instead, analysis of CSOs' UPR discourse reveals that HRDs face a raft of rights violations, including threats, violence and murder. Their work is being curtailed by increasing state restrictions on freedom of association and expression. The malaise is compounded by impunity for offenders, corrupt practices and governments' failure to respond to earlier UPR recommendations. The analysis shows a strong gendered dimension to HRD oppression with women HRDs particularly vulnerable to all types of violation. These findings underline the extension to South Asia of what international analysis elsewhere has dubbed a 'counter-associational revolution', or the rise, spread and contagion of restrictive legislation. This threat to democracy in the region shows that key reforms are urgently required, including measures to ensure the justiciability of the UN Declaration on HRD.